The analysis of viability for mammalian cells treated at different temperatures and its application in cell shipment. - Juan Wang; Yun Wei; Shasha Zhao; Ying Zhou; Wei He; Yang Zhang; Wensheng Deng (PLoS ONE, 2017)
Mammalian cells are very important experimental materials and widely used in biological and medical research fields. It is often required that mammalian cells are transported from one laboratory to another to meet with various researches. Conventional methods for cell shipment are laborious and costive despite of maintaining high viability. In this study we aimed to develop a simple and low-cost method for cell shipment by investigating the viabilities of different cell lines treated at different temperatures. We show that the viability of mammalian cells incubated at 1°C or 5°C significantly reduced when compared with that at 16°C or 22°C. Colony formation assays revealed that preservation of mammalian cells at 1°C or 5°C led to a poorer recovery than that at 16°C or 22°C. The data from proliferation and apoptotic assays confirmed that M2 cells could continue to proliferate at 16°C or 22°C, but massive death was caused by apoptosis at 1°C or 5°C. The morphology of mammalian cells treated under hypothermia showed little difference from that of the untreated cells. Quantitative RT-PCR and alkaline phosphatase staining confirmed that hypothermic treatment did not change the identity of mouse embryonic stem cells. A case study showed that mammalian cells directly suspended in culture medium were able to be shipped for long distance and maintained a high level of viability and recovery. Our findings not only broaden the understanding to the effect of hypothermia on the viability of mammalian cells, but also provide an alternative approach for cell shipment.